2008
DOI: 10.1182/blood-2007-05-092718
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-24 inhibits erythropoiesis by targeting activin type I receptor ALK4

Abstract: IntroductionErythropoiesis is the complex process during which a fraction of primitive multipotent hematopoietic stem cells become committed to the red cell lineage, undergoing erythroid progenitors (burstforming unit erythroid [BFU-E] and colony-forming unit erythroid [CFU-E]), normoblasts, erythroblasts, reticulocytes, and ultimately differentiating to mature erythrocytes. 1 This process is regulated by various factors such as erythropoietin, testosterone, estrogen, interleukin-3, granulocyte-macrophage col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 36 publications
1
138
0
2
Order By: Relevance
“…As reported recently, miRNAs are abundant, small non-coding RNAs that mediate sequence-specific, posttranscriptional gene expression by binding to the target 3 0 UTR of mRNA, and have been implicated in the regulation of certain cancer-related processes, including development, differentiation, apoptosis and proliferation (Merkerova et al, 2008;Ruan et al, 2009;Yang et al, 2009). To date, miR-24 has been implicated in the regulation of hematopoietic differentiation and cell proliferation (Lal et al, 2008(Lal et al, , 2009Wang et al, 2008). For example, miR-24 downregulates the expression of human dihydrofolate reductase and expression of miR-24 is upregulated during differentiation of human leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…As reported recently, miRNAs are abundant, small non-coding RNAs that mediate sequence-specific, posttranscriptional gene expression by binding to the target 3 0 UTR of mRNA, and have been implicated in the regulation of certain cancer-related processes, including development, differentiation, apoptosis and proliferation (Merkerova et al, 2008;Ruan et al, 2009;Yang et al, 2009). To date, miR-24 has been implicated in the regulation of hematopoietic differentiation and cell proliferation (Lal et al, 2008(Lal et al, , 2009Wang et al, 2008). For example, miR-24 downregulates the expression of human dihydrofolate reductase and expression of miR-24 is upregulated during differentiation of human leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs participate in the regulation of erythropoiesis: miR-221/222 inhibit normal erythropoiesis and erythroleukemic cell growth down-regulating kit receptor expression, 28 miR-24 hampers erythropoiesis by targeting ALK4 and perturbing activin signaling, 39 miR-320 finely tunes the translational activities of CD71 in reticulocytes, 20 c-Myb and miR-15a form an autoregulatory feedback loop which govern the transition from BFU-E to CFU-E stage. 40 Our results suggest that also miR-223 belongs to a functional set of miRNAs implicated in fine-tuning the expression of key genes to a physiologically relevant level during erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 43 showed that miR-24 could decrease human ACVR1B expression at mRNA and protein levels. Published evidence 46 showed that this miR-24 is involved in the inhibition of skeletal muscle differentiation by TGFb.…”
Section: Discussionmentioning
confidence: 99%